National productivity boards after seven years - Garcia, Luis,Leodolter, Alexander,Turrini, Alessandro (Publications Office of the European Union, 2024)
National Productivity Boards (NPBs) aim to foster debate relating to productivity and competitiveness and enhance policy making in these areas. In 2016, the Council of the European Union called on all euro area Member States to set up an NPB with characteristics such as independence and capacity to carry out high-quality analyses. The non-euro area Member States were also encouraged to establish similar bodies. More than seven years after the adoption of the NPB recommendation, the network of NPBs is well established. Through the annual reports, NPBs discuss productivity trends, productivity drivers and policies as well as economic developments with an impact on productivity and competitiveness. In most cases, NPB characteristics are broadly in line with those of the recommendation. However, not all EU Member States have an NPB in place and there are considerable differences in NPBs' institutional design, capacity, and involvement in policy making. This paper updates the assessment made in the 2019 and 2021 European Commission progress reports on the implementation of the NPB recommendation. It also identifies gaps with respect to additional criteria for NPB effectiveness found in the existing literature, this being its main novelty. Findings suggest that NPBs would especially benefit from stronger provisions to guarantee independence and adequate resources and from practices boosting their participation in domestic policy making.
10.2765/8943
Keywords: Graue Literatur; National Productivity Boards; productivity; competitiveness; economic policy; innovation; policymaking